2021
DOI: 10.1101/2021.06.23.449389
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A cattle graph genome incorporating global breed diversity

Abstract: Despite only 8% of cattle being found in Europe, European breeds dominate current genetic resources. This adversely impacts cattle research in other important global cattle breeds. To mitigate this issue, we have generated the first assemblies of African breeds, which have been integrated with genomic data for 294 diverse cattle into the first graph genome that incorporates global cattle diversity. We illustrate how this more representative reference assembly contains an extra 116.1Mb (4.2%) of sequence absent… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 83 publications
5
17
0
Order By: Relevance
“…No duplications, inverted duplications and translocations passed the quality filtering. Consistent with results from previous studies 28 , most of the post-filtering insertions and deletions identified fell into the smaller classes, though 1,796 SVs (403 deletions, 1,389 insertions and 4 inversions) of over 50kb in length were identified (Figure 1).…”
Section: Technical Validationsupporting
confidence: 89%
“…No duplications, inverted duplications and translocations passed the quality filtering. Consistent with results from previous studies 28 , most of the post-filtering insertions and deletions identified fell into the smaller classes, though 1,796 SVs (403 deletions, 1,389 insertions and 4 inversions) of over 50kb in length were identified (Figure 1).…”
Section: Technical Validationsupporting
confidence: 89%
“…Sequencing technologies and assemblers evolve rapidly, and so even recently generated bovine assemblies, including the ones reported here, have been produced under non-uniform conditions (e.g., (Crysnanto et al, 2021; Talenti et al, 2021)). Given the differences we observed between HiFi- and ONT-based assemblies, especially in comparison to the CLR-based ARS-UCD1.2 reference, it was crucial to examine how pangenome construction responded to different assembly inputs.…”
Section: Resultsmentioning
confidence: 99%
“…Larger structural variants (SVs) and variation located in repetitive or challenging regions have rarely been studied across Bovinae due to the inherent limitations of short sequencing reads and incomplete reference genomes. Moreover, no reference assembly of a single individual can reflect the immense genomic diversity present in global breeds of domestic cattle (Crysnanto et al, 2019(Crysnanto et al, , 2021Crysnanto & Pausch, 2020;Talenti et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This progression is already afoot, particularly for targets that involve complex variation, such as cancer (The Computational Pan-Genomics Consortium, 2016), plant pangenomics (Bayer et al ., 2020; Liu et al ., 2020; Qin et al ., 2021; Li et al ., 2022; Bayer et al ., 2022), and metagenomics (Zhong et al ., 2021). Also, when studying animals like bovines (Leonard et al ., 2021; Talenti et al ., 2022; Bovine Pan-Genome Consortium, 2022).…”
Section: Discussionmentioning
confidence: 99%